HUBUNGAN MEAL SKIPPING DAN FREKUENSI MAKAN TERHADAP STATUS GIZI PADA REMAJA DI SMA NEGERI 47 JAKARTA - Alivia Monica Kristy (2020)
Adolescence is a life cycle with poor eating behaviour including meal skipping, increased intake of snacks and fast food, and decreased intake of dietary fiber, and increased vulnerability to obesity. Meal skipping and eating frequency may effect nutritional status of adolescent through total energy intake and increased risk of metabolic diseases in adulthood. The study was performed to analyze the correlation between meal skipping and eating frequency with nutritional status in adolescent at SMA Negerti 47 Jakarta. This study collected data since April 2020 from 80 respondent and used a cross sectional study as a method design. The sampling was organized by using stratified sampling based on class. Frequencies of skipping meals, eating frequency, and body weight and height assessed by using online questionnaire, meanwhile, meal pattern assessed by using estimated food record for three days. According to the results there is a relationship between meal skipping with nutritional status (p=0,005) but from three main meals only breakfast has relationship with nutritional status (p=0,005) and eating frequency with nutritional status (p=0,000). Keyword : Meal skipping, eating frequency, snacking, nutritional status, adolescence